2017
DOI: 10.22161/ijeab/2.4.73
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Determinants of Entrepreneurship Decision among Yam Agribusiness Entrepreneurs in Benue State, Nigeria.

Abstract: Abstract-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…The positive sign of the coefficient conforms to the a priori expectation, implying that if a marketer is a male, his level of investment in the marketing of value-added products of cassava increases by ₦11,566.36. Male agripreneurs usually have opportunity for investment capital translating to more investment compared to their female counterparts (Okeke et al, 2015). This is congruent with the finding of Mutinda et al (2020) who revealed that being male increased the probability of investment and attributed it to male agripreneurs having better networks in society which place them in better positions to get more information and new production techniques compared to females.…”
Section: Determinants Of Investment Decision and Level Of Investment ...supporting
confidence: 75%
See 4 more Smart Citations
“…The positive sign of the coefficient conforms to the a priori expectation, implying that if a marketer is a male, his level of investment in the marketing of value-added products of cassava increases by ₦11,566.36. Male agripreneurs usually have opportunity for investment capital translating to more investment compared to their female counterparts (Okeke et al, 2015). This is congruent with the finding of Mutinda et al (2020) who revealed that being male increased the probability of investment and attributed it to male agripreneurs having better networks in society which place them in better positions to get more information and new production techniques compared to females.…”
Section: Determinants Of Investment Decision and Level Of Investment ...supporting
confidence: 75%
“…This is in consonance with Nwibo and Alimba (2013) who opined that educated individual has better potential to choose the area to invest as he/she knows the nitty-gritty of investment. Similarly, Okeke et al (2015) reported a positive relationship between educational status and investment decision and attributed this to better understand of the risks and uncertainties found in business.…”
Section: Determinants Of Investment Decision and Level Of Investment ...mentioning
confidence: 97%
See 3 more Smart Citations